Influence of silver nanoparticles on the Dy3+ luminescence properties in TeO2-ZnO-BaO glasses. (2018) - Ruangtaweep, Y.; Yasaka, P.; Rajagukguk, J.; Kaewkhao, J.
Abstract: The influence of silver nanoparticles (AgNPs) on the Dy 3+ luminescence properties in tellurite glasses has been investigated. The glass samples with chemical composition of (54-x(TeO2 : 10ZnO: 35BaO: 1.0Dy2 O3 : xAgNPs (where x= 0.00, 0.01, 0.02, 0.03, 0.04, and 0.05% by mol) were prepared by the conventional melt quenching technique at 950 °C in normal atmosphere. The results show that the excitation and emission intensity of glass samples are decreased with increasing of AgNPs concentrations. The excitation spectra were obtained by monitoring in the wavelength region 250–550 nm at emission wavelength 575 nm. The excitation bands are identified at 325, 352, 365, 388, 425, 453 and 473 nm corresponding to the transitions from the ground state 6 H5/2 to 6 P3/2, 6 P7/2, ( 4 I11/2 + 4 P3/2 ), ( 4 I13/2 + 4 F7/2 ), 4 G11/2, 4 I15/2 and 4 F9/2 excited states, respectively. The emission spectra were recorded in the wavelength region 500–750 nm using 352 nm excited wavelength. The emission peaks are observed at 483 (blue), 575 (yellow) and 665 (red) which are attributed to 4 F9/2 ® 6 H15/2, 4 F9/2 ® 6 H13/2, and 4 F9/2 ® 6 H11/2 transitions, respectively.